The influence of Problem Reality-Based Web Course Learning (WCL) on students' Higher-Order Thinking Skills (HOTS) on human reproductive system material - Anggun Firma Rahmawati; Irma Yuniar Wardhani (Universitas Ahmad Dahlan, 2022)
The purpose of this study was to describe 1) the application of Problem Reality Based Web Course Learning in the Reproductive System Material for Class XI MIPA SMA 1 Bae Kudus. 2) the students' High Order Thinking Skills on Reproductive System Material for Class XI MIPA SMA 1 Bae Kudus. 3) the effect of Web Course Learning Based on Problem Reality for Higher Order Thinking Skills of students XI MIPA on Reproductive System material SMA 1 Bae Kudus. This is experimental research with a quantitative approach. The sample of this study used 70 students from SMA 1 Bae Kudus. Sampling by using the Cluster Random Sampling technique. The data analysis by using the Independent sample t-test. Hypothesis test results show that the value of sig-2 Tailed 0.000 <0.05, the conclusion is that H 1 is accepted, meaning that there is an effect of implementation Web Course Learning Based on Problem Reality for Higher Order Thinking Skills of students XI MIPA on Reproductive System material. This research is expected to be able to provide new results that online learning is able to increase Higher Order Thinking Skills of student.